EXPLORING STUDENTS’ PERCEPTIONS OF SUSTAINABILITY AS PART OF THEIR CLOTHING AND TEXTILE CURRICULUM - Patnaik, Sweta (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Sustainability has been a determining factor for individuals because of various reasons for decades, be it climate change, and environmental pollution. Clothing has been a need for us and is now part of everyday life either in the form of fashion, seasonal wear, trend, and the like. The analysis revolved around students’ responses to questions following the inclusion of sustainability within the curriculum as part of an engineering curriculum. The results show that “Sustainability” - a new term/concept being included within the clothing and textile curriculum at the advanced diploma stage. Therefore, it is essential to create awareness and let the students know regarding sustainability by including it in the curriculum. This paper highlights the inclusion of sustainability within the Advanced Diploma qualification of the clothing and textile curriculum. This paper reflects the need for curriculum development by assimilating sustainable elements in the above-mentioned qualification, so that upcoming professionals can embody sustainability to create an environmentally friendly and sustainable society to live in.